EVALUASI PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN BOGOR SELATAN KOTA BOGOR - Maya Dehani; Denny Hernawan; Irma Purnamasari (LPPM Universitas Djuanda Bogor, 2018)
The purpose of this study is to know the Keluarga Harapan Program (PKH) in Bogor Selatan District Bogor City. The theory used in this research is by using policy evaluation of William N. Dunn which states that to measure the success of a program evaluation can be measured through six variables namely: effectiveness, efficiency, adequacy, equity, responsiveness, accuracy.The method used is descriptive analysis using Qualitative approach. While the data analysis technique used is by using Interactive model developed by Miles and Huberman, which includes data reduction, datadisplay, and conlusiondrawing / verification. Data collection techniques used were interviews, direct observation and documentation. The informants that the researchers took were 2 kinds of informants, the first PKH assistant who was taken by 2 persons, namely the active companion and the less active companion, and the second informant, the PKH participant who was taken 3 people, the participants who had long been the PKH participants, just become PKH participants and participants who complete the PKH component.The result of this research can be concluded that the process of PKH implementation has been running well in accordance with the purpose of launching PKH in the hope of solving the classical problems faced by RTSM such as malnutrition, high maternal and infant mortality and low participation of school age children. The target achieved in the implementation of family planning program (PKH) in the district of South Bogor is in the form of the incapability of the community is not able especially RTSM in meeting the needs of life related to education, health of pregnant women and toddlers. Keywords: Evaluation, Program, Poverty.